Lending an Ear: iPeer2Peer plus Teens Taking Charge online self-management to empower adolescents with arthritis in Ireland: protocol for a pilot randomised controlled trial - Stephanie Haugh; Line Caes; Brian E McGuire; Caroline Heary; Siobhan O'Higgins; Jennifer Stinson; Sara Ahola Kohut; Laura O'Connor; Brian Slattery; Michelle Hanlon; Hannah Durand (BMJ Open)
Introduction Juvenile idiopathic arthritis (JIA) negatively affects adolescents’ everyday activities. To address the need for innovative, effective, convenient, low-cost psychosocial self-management programmes, we developed an Irish version of Canadian Teens Taking Charge (TTC) and integrated it with Skype-based peer support iPeer2Peer (iP2P).Objectives To explore the feasibility and preliminary outcome impact (effectiveness) of an integrated iP2P and Irish TTC, via three-arm (treatment as usual, TTC and iP2P–TTC) pilot randomised controlled trial (RCT); and determine feasibility and sample size for a full RCT. To ensure active involvement of adolescents with JIA via a Young Person Advisory Panel and examine how participants experienced the study. Finally, to see if TTC and iP2P with TTC reduce costs for families.Methods and analysis Recruitment of 60 families will be ongoing until July 2019, via healthcare professionals and support groups. Analysis will consist of single-blinded (outcome assessment), three-arm pilot RCT, using online questionnaires, with assessments at baseline (T1), after intervention (T2) and 3 months post-intervention (T3). The primary outcomes on feasibility with comparisons of TTC and iP2P–TTC on fidelity, acceptability and satisfaction, engagement and degrees of tailoring. The secondary outcomes will be self-management and self-efficacy and a range of health-related quality-of-life factors, pain indicators and costs.Participants from the intervention groups will be invited to share their perspectives on the process in semistructured interviews. Quantitative data will be analysed using SPSS V.21 and the audio-taped and transcribed qualitative data will be analysed using qualitative content analysis.Dissemination Via journal articles, conference presentations, co-delivered by key stakeholders when possible, launch of accessible, effective and sustainable Internet self-management and peer support for Irish adolescents with JIA.Trial registration number ISRCTN13535901; Pre-results.